Correlations between the Senior High School Grade 12 Students’ Perception of School Classroom Climate and Compliance to School Classroom Norms in a Private University in Manila, Philippines - Ahorro , Adrian Miguelle T.; David , Ma. Rafaella T.; Molina, Joaquin Maria V.; Pangilinan, Aimee Breanna Y.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2021)
This quantitative study aimed to determine the correlation between senior high school Grade 12 students’ perception of school climate and compliance with school classroom norms in a private university in Manila, Philippines. A sample of 249 Grade 12 respondents who were randomly selected answered the online self-administered questionnaire composed of modified scales to explore the two variables, with Cronbach tests exhibiting an acceptable level of internal consistency (perceptions school climate = 0.88, compliance of classroom norms = 0.86). The study found a positive perception of school climate (M = 4.19, SD = 0.40) and a very high level of classroom norm compliance (M = 3.40, SD = 0.32) among the respondents. The Pearson R test revealed a significant moderate positive correlation between their perception of school climate and their level of school classroom norm compliance and (r = 0.554, p < 0.001). This implies that their compliance or adherence to school classroom norms increases as their perception of school climate positively increases.